Perlindungan Hukum Terhadap Notaris yang Melaporkan Pihak-Pihak dalam akta yang Terindikasi Tindak Pidana Pencucian Uang (TPPU) - Nadya Yusvira; Fitra Deni; Yoga Satrio (CV Rewang Rencang, 2025)
This research is a decision of application of the obligation for notary to report about money laundering, where If we examine and analyze the definition of a Notary as stated in Article 1 of Law Number 2 of 2014 concerning the Amendment to Law Number 30 of 2004 on the Position of Notary, the definition of a Notary is a Public Official who has the authority to create authentic deeds and other authorities based on further regulations. In carrying out their duties, a Notary, in accordance with their oath of office, has an obligation as stated in Article 16, paragraph 1 of Law Number 2 of 2014, which stipulates that a Notary, in performing their duties and position, must act with trust, honesty, caution, independence, impartiality, and protect the interests of the parties involved in the legal act. In interpreting Article 16, paragraph 1 of Law Number 2 of 2014, the clause